If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = -8 + -9y Solving 16 = -8 + -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. 16 + 9y = -8 + -9y + 9y Combine like terms: -9y + 9y = 0 16 + 9y = -8 + 0 16 + 9y = -8 Add '-16' to each side of the equation. 16 + -16 + 9y = -8 + -16 Combine like terms: 16 + -16 = 0 0 + 9y = -8 + -16 9y = -8 + -16 Combine like terms: -8 + -16 = -24 9y = -24 Divide each side by '9'. y = -2.666666667 Simplifying y = -2.666666667
| 7a-7b=15whatisA-B | | 3/4K-6=2k+5 | | -36a^5b^4/16a^-5b^2 | | Thiswebsiteusescookiestoensureyougetthebestexperienceonourwebsite.Moreinfo5x^2+7=9x/2 | | 15p-30= | | -10x=-24 | | 8-4/x-2=-1/2 | | x+12x=-32 | | 11r=13-2 | | -15x+54=0 | | -3n+2=0 | | 2/5r=13-4r2 | | 1/12m−1/6=1/4m+12 | | t-79=184 | | 8p+10=-4+6 | | 3/4x^2-7x+9 | | -2+8y=-6 | | 15a/25a | | (x+3)(4x-16)=0 | | 2/5h-7=13 | | Y=-2x^2-12x-23 | | 1.875=5/8(b-5) | | 12x+16=31 | | b/3=3 | | u/8=2 | | 6(y-3)=2(19-y) | | c-9=3/4c | | t/4=32 | | 2y-(13-2y)=59 | | (x+2)+y= | | 6r+4s= | | (143(5)+67)=5 |